An assessment of the effectiveness of speed humps as a traffic calming measure for accident reduction in Durban - Monyatsi, Lemohang (Department of Civil Engineering, 2021)
EThekwini municipality has been allocating millions of rands each year for speed humps as a traffic calming measure, to curb rat-running and ensure pedestrian safety in the city. Since 2012, the city has spent R42.1 million of its capital budget on speed humps. Despite all traffic calming efforts, there hasn't been significant changes in the city's total accidents. Between 2000 and 2015, the city's total crashes has never been below 50 000 per annum. In terms of injuries, the same trend can be observed. Person injuries have been increasing year-on-year since 2012. To date, there hasn't been a study conducted by EThekwini Municipality to assess the effectiveness of these speed humps implemented across the city. At the moment, despite the city's annual commitment to implement traffic calming, particularly in the form of speed humps, the city does not have an idea as to whether traffic calming measures put in place are successful or not, or whether they are effecting any changes at all. This research, therefore, aims to use information available to assess changes in specific roads, i.e. roads that have been traffic calmed. The study will look at these numbers which are key performance indicators before and after the implementation of speed humps. This study will assess the impact of reactive (responsive to requests) traffic calming in the form of speed humps using accident data. The assessment will look at changes relating to the number of crashes before and after implementation of speed humps, it will also focus on changes in the severity of accidents involved. The research will study changes in relation to the types of accident involved particularly pedestrians. These key performance indicators (KPIs) will be used to assess changes and answer the question of effectiveness.